Postoperative Musculoskeletal Imaging and Interventions Following Hip Preservation Surgery, Deformity Correction, and Hip Arthroplasty - Samim, Mohammad; Khodarahmi, Iman; Burke, Christopher; Fritz, Jan (The Journal of Hip Surgery, 2024)
Total hip arthroplasty and hip preservation surgeries have substantially increased over the past few decades. Musculoskeletal imaging and interventions are cornerstones of comprehensive postoperative care and surveillance in patients undergoing established and more recently introduced hip surgeries. Hence the radiologist's role continues to evolve and expand. A strong understanding of hip joint anatomy and biomechanics, surgical procedures, expected normal postoperative imaging appearances, and postoperative complications ensures accurate imaging interpretation, intervention, and optimal patient care. This article presents surgical principles and procedural details pertinent to postoperative imaging evaluation strategies after common hip surgeries, such as radiography, ultrasonography, computed tomography, and magnetic resonance imaging. We review and illustrate the expected postoperative imaging appearances and complications following chondrolabral repair, acetabuloplasty, osteochondroplasty, periacetabular osteotomy, realigning and derotational femoral osteotomies, and hip arthroplasty.
Keywords: magnetic resonance imaging; computed tomography; hip; surgery; arthroplasty